AutomationML : The Industrial Cookbook - Ashtari, Behrang; Bartelt, Matthias; Behnert, Anna-Kristin; Biffl, Stefan; Blume, Jan-Wilhelm; Braun, Dominik; Dorofeev, Kirill; Drath, Rainer; Drath, Rainer; Gehlen, Lukas; Graf, Andreas; Hinze, Jörg; et al. (De Gruyter Oldenbourg, 2021)
This book provides a comprehensive in-depth look into the practical application of AutomationML Edition 2 from an industrial perspective. It is a cookbook for advanced users and describes re-usable pattern solutions for a variety of industrial applications and how to implement it in software. Just to name some: AutomationML modelling of AAS, MTP, SCD, OPC UA, Automation Components, Automation Projects, drive configurations, requirement models, communication systems, electrical interfaces and cables, or semantic integration aspects as eClass integration or handling of semantic heterogeneity. This book guides through the universe of AutomationML from industrial perspective. It is written by AutomationML experts that have industrially implemented AutomationML in pattern solutions for a large variety of applications. This book is structured into three major parts. • Part I: software implementation for developers • Part II: re-usable industrial pattern solutions and domain models • Part III: outlook into future AutomationML applications Additional material to the book and more information about AutomationML on the website: https://www.automationml.org/about-automationml/publications/amlbook/